Nest predation of Cory's shearwater Calonectris borealis (Aves, Procellariiformes) by introduced mammals on Terceira Island, Azores - Lucas Lamelas-Lopez; Marco Ferrante; Paulo Borges; Isabel Amorim do Rosário; Veronica Neves (Biodiversity Data Journal, 2023)
The Azores holds the largest population of Cory's shearwater Calonectris borealis (Cory, 1881) (Aves, Procellariiformes) in the world. Apart from a few mammal-free islets, the bulk of the population breeds in coastal areas on the main human-inhabited islands, where several non-native predators have been introduced. Throughout the entire year of the 2019 breeding season, we used motion-triggered cameras and regularly visited three colonies of Cory's shearwater to identify nest predators and the factors affecting nest predation. A total of 292,624 photos were obtained, of which 97.7% were of Cory’s shearwaters, 1.7% of non-target species (e.g. other birds, rabbits) and 0.52% of potential predators. Of the monitored nests, 25.7% were predated (n = 9), mainly by black rats (n = 8), but also by cats (n = 1). The relative abundance of black rats in the nests was the main factor explaining nest mortality. This variable was significantly and negatively related with the daily survival rate of Cory’s shearwater nestlings. Identification of the main nest predators is crucial for the management and conservation of native bird populations, particularly on oceanic islands, which harbour an important number of threatened and endemic species.